Contagion in the interbank network: An epidemiological approach - Mervi Toivanen (Bank of Finland, 2013)
This paper analyses the importance of individual bank-specific factors on financial stability. First, we use a novel method to model the spreading of the contagion in the interbank network by implementing an epidemiologic model. Actual data on European banks is exploited with simulated scale-free networks. The average contagion affected 70% and 40% of European banks' total assets in 2007 and in 2010, respectively. Country-level results suggest that French, British, German and Spanish banks are the most contagious ones, whereas banks from Ireland, Greece and Portugal induce only limited negative effects. Secondly, cross-sectional panel estimations are performed to disentangle the leading indicators influencing the level of contagion. Bank clustering, large in-coming interbank loans and bank reputation are more prominent explanatory variables than the size or leverage. Finally, central banks' interventions reduce contagion only slightly.
URN:NBN:fi:bof-20140807192
Keywords: G01; G21; C15; 330; contagion; banks; Europe; interbank; epidemiology; panel regression